2021
DOI: 10.1371/journal.pone.0245736
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of interest policies at Belgian medical faculties: Cross-sectional study indicates little oversight

Abstract: Background Medical students encounter pharmaceutical promotion from the very start of their training. Medical schools have an important role to play in educating medical students regarding the interactions between healthcare professionals (HCPs) and industry and in protecting them from commercial influence and conflict of interest (COI). In 2019, medical student associations in Belgium and abroad called for more preparation in dealing with COI and for a more independent medical training. As little information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This was instrumental in raising awareness on COI among academic institutions; for example, the media attention generated by the AMSA scorecard influenced the development of COI policies in several US medical schools [ 8 ] and the institutional scores have improved year after year likely due to these rankings. Moreover, the AMSA scorecard has since been adapted and used in similar studies conducted in Australia, Belgium, Canada, France, and Germany [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was instrumental in raising awareness on COI among academic institutions; for example, the media attention generated by the AMSA scorecard influenced the development of COI policies in several US medical schools [ 8 ] and the institutional scores have improved year after year likely due to these rankings. Moreover, the AMSA scorecard has since been adapted and used in similar studies conducted in Australia, Belgium, Canada, France, and Germany [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the studies were conducted in North America and little is known about COI policies at European medical schools apart from the three studies from Central Europe [ 9 , 11 , 13 ]. We therefore decided to investigate the content and strength of COI policies at Scandinavian medical schools.…”
Section: Introductionmentioning
confidence: 99%
“…One way to improve COI management and reporting is to include the concepts of COI as an integral part of medical students’ undergraduate curriculum and education ( Andresen et al ., 2017 ; Bechoux et al ., 2021 ; Deis et al ., 2020 ), thus, avoiding COI cases among pharmacists who are likely to become future researchers and experts working with the drug industry. A previous study from Jordan showed that the majority of graduating-year pharmacy students were unaware of COI, which was related to the limited coverage of COI concepts in their pharmacy curriculum ( Ababneh et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 The US experience also attracted international attention, with subsequent studies on medical school COI policies conducted in Canada, Germany, France and Belgium. [20][21][22][23] A recent systematic review found extensive variation in COI policies at medical schools in high-income countries, with no published research in low-and middle-income countries. 24 The systematic review concluded that there was weaker oversight of COI in medical education in Europe than in North America.…”
Section: Introductionmentioning
confidence: 99%
“…Following this public attention, many academic institutions across the United States strengthened their COI policies 18 . The US experience also attracted international attention, with subsequent studies on medical school COI policies conducted in Canada, Germany, France and Belgium 20–23 . A recent systematic review found extensive variation in COI policies at medical schools in high‐income countries, with no published research in low‐ and middle‐income countries 24 .…”
Section: Introductionmentioning
confidence: 99%